Diseño de Albergue Nomada (2024)
The complexity of this has to do with the fact of feeling lost, while the simplicity of it has to do with the fact of feeling lost. "(M aeda, 2008, p. 61). The design of tents has come a long way, going from simple shelters to structures that offer m More than weather protection. This project focuses on ORI, a line of camping products that seeks to be more practical, easy to use and comfortable for those who enjoy camping. Inspired by origami, ORI combines a simple structure with the versatility necessary to improve the camping experience.